Biopower and the reproductive autonomy of childfree women in South Africa - Van Zyl, Elize (My University, 2020)
The current research sought to examine the discourses employed by medical practitioners regarding women’s reproductive autonomy, with specific reference to voluntary sterilisation. Furthermore, the researched aimed to investigate whether these discourses were in favour of pronatalist ideologies withing society. It also aimed to challenge the status quo by exploring the power inequalities that may exist within medicine, with specific attention paid to nuances concerning race, class, and gender within the context of semi-structured interviews. The semi-structured interviews conducted included questions regarding medical practitioners’ views on women and motherhood in general, how the female body is viewed within medicine, and voluntary sterilisation. The research is situated within the critical theory paradigm and employs assumptions of social constructionism. The data were analysed by applying the critical discourse analysis approach within the Foucauldian tradition, utilising Parker’s (1992) steps for analysing discourses. The major themes that emerged included Discourses of women and motherhood, Discourses surrounding the medical practitioners, and Discourses surrounding voluntary sterilisation, each with several subthemes. The emerging themes revealed that there exist many contradicting and interlinked discourses, both on a societal and medical level, through which women and motherhood are constructed and can be understood. Mainly, the research revealed that while women are constructed as having complete autonomy over their reproductive decisions, their choices are deeply influenced, controlled, and limited by the prescribed identities made available to them through discourse
Biopower reproductive autonomy childfree women
A research project submitted in partial fulfilment of the requirements for the degree of MA by coursework and Research Report in the field of Psychology in the Faculty of Humanities, University of Witwatersrand, 2020